Utilization of acute medical services in general practice: a retrospective routine data analysis - Christoph Strumann; Wolfgang C. G. von Meißner; Paul-Georg Blickle; Johannes Rieken; Jost Steinhäuser (International Journal of Emergency Medicine)
Abstract Background The increasing utilization of emergency departments by patients with acute but non-emergency medical needs contributes to overcrowding in emergency care. Previous research has mainly focused on hospitals and out-of-hours care centres. The role of general practitioners providing primary care during office hours for emergency and acutely ill patients has not yet been considered intensively. This analysis aimed to quantify and describe the documented outpatient utilization behaviour of patients with acute care needs in primary care practices during office hours. Methods The retrospective cohort study used routine data from 16 German primary care practices in 2022 and 2023 from the Supraregional Health Service Research Network. Acute care cases were identified as consultations without a prior appointment or those with a same-day appointment. Statistical analyses included bivariate and multivariate analyses. Results A total of 873,732 consultations involving 90,020 patients were analysed. When considering only the first visit of an acute episode, 60.6% of cases were classified as acute. Patients seeking acute care were younger (51.9 vs. 58.3 years, p < 0.001) and more likely to visit the practice on Mondays (Odds Ratio: 1.48, p < 0.001) or at the weekend (Odds Ratio: 13.91, p < 0.001). Nonspecific health factors, respiratory-, musculoskeletal- and cardiovascular reasons for encounter dominated. The majority of acute cases (80%) did not seek any further health service on the same day, while approximately 19% of patients were referred to a specialist and 3% were admitted to a hospital within 14 days. Conclusion The effective management of acute cases by primary care practices highlights the potential for strengthening this sector to enhance the quality and efficiency of emergency care.